Factors Influencing Wellbeing among Working Mothers of Small and Medium Enterprises in Europe: The Moderating Role of Supervisory Support - Choo, Eern Yie (SEISENSE (PRIVATE) LIMITED, 2023)
Purpose- It is known that working mother faces work-family responsibilities that likely affect their well-being. There is also a few research on conflict differentiated by work status and gender or on the moderating role of perceived supervisor support. Therefore, there is a research gap in this topic. The purpose of this research is to examine the working mother’s wellbeing among the small and medium enterprises in Europe.Design/Methodology- In this research, independent variables such as job resources, inter-role work and family conflict, working environment and underemployment are being discussed to determine their correlation with employee’s wellbeing, based on findings from Eurofound’s sixth European Working Condition Survey 2015 (EWCS). Multiple Linear Regression was conducted to investigate the influence between identified variable.Findings- The research found that the roles of supervisory support do affect some of the variables. Appropriate supervisory intervention relieves job stress and increases the wellbeing for employed mother. Wellbeing and work are closely related, in that the bad or good environment of working have a direct impact on employed mother’s quality of life.Practical Implications- The study contributes to a better understanding of work-family conflict and their wellbeing. This report could provide valuable insight to organizations on ways to ensure effectiveness and better performance by preventing conflict from occurring